Radiocarbon ages of sediment core samples from the Bay of Bengal - Hein, Christopher; Weber, Michael (IEDA: EarthChem Library, 2018)
Abstract: This dataset is a compilation of new and previously reported results from accelerator mass spectrometry (AMS) radiocarbon dating of planktonic foraminifera from sediment core samples collected during cruise SO93 on R/V Sonne in the Bay of Bengal. These data are used to create an age model for the sediment cores. Other Description: Hein, C.J., Galy, V., Galy, A., France-Lanord, C., Kudrass, H., & Schwenk, T., (2017), "Post-glacial climate forcing of surface processes in the Ganges–Brahmaputra river basin and implications for carbon sequestration." Earth and Planetary Science Letters, 478: 89–101